5(x+6)=4x+3

Simple and best practice solution for 5(x+6)=4x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+6)=4x+3 equation:


Simplifying
5(x + 6) = 4x + 3

Reorder the terms:
5(6 + x) = 4x + 3
(6 * 5 + x * 5) = 4x + 3
(30 + 5x) = 4x + 3

Reorder the terms:
30 + 5x = 3 + 4x

Solving
30 + 5x = 3 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
30 + 5x + -4x = 3 + 4x + -4x

Combine like terms: 5x + -4x = 1x
30 + 1x = 3 + 4x + -4x

Combine like terms: 4x + -4x = 0
30 + 1x = 3 + 0
30 + 1x = 3

Add '-30' to each side of the equation.
30 + -30 + 1x = 3 + -30

Combine like terms: 30 + -30 = 0
0 + 1x = 3 + -30
1x = 3 + -30

Combine like terms: 3 + -30 = -27
1x = -27

Divide each side by '1'.
x = -27

Simplifying
x = -27

See similar equations:

| -5=26w | | -7u=-22 | | 57=-y/4 | | 2/(3-2x)=1 | | x=y^2+7y+c | | 0=-x^2-6x-3 | | 8=x+(x+92) | | I=P(r+nt) | | 5x+2x=1260 | | 5(x+2)+12=-24 | | 5x-3/9 | | 3x-7+9-2x=28 | | (3+i)z^2+(5-5i)z+(-2+16i)=0 | | 2/3x-25=-29 | | 4x+3y=2x-6y | | (1+x^2)dy=(1+xy)dx | | 7y-12=4y+2 | | X^2+100x-15000=0 | | 9z-6-5z=-14 | | 0.7x-0.6(50+x)=-0.44(50) | | 15sinx+8cosx=this(x-a) | | 5b+20=10b | | 25-6x=-29 | | 9(m-4)-8(m+2)=-52 | | 3a+4b=70 | | 7-(4z-1)=2-5z | | 3a+4b=35 | | (2k+1)(xsquare+1)=(2k+5)x | | a-21/x=4 | | x-21/x=4 | | x^6-9x^5+30x^4-50x^3+45x^2-21x+4=0 | | x^2-7*x=0 |

Equations solver categories